Circular RNAs at the crossroads of acute pancreatitis: bridging molecular mechanisms to diagnostic and therapeutic innovations - Chen, Jing; Chen, XiaoLing; He, Fei (Frontiers in Genetics, 2025)
Acute pancreatitis (AP) is a severe inflammatory condition that frequently leads to systemic inflammatory response syndrome and multiple organ failure. Despite the increasing occurrence, targeted therapies remain unavailable. CircRNAs have recently been implicated in AP pathogenesis, regulating biological processes such as apoptosis, pyroptosis, and inflammation through mechanisms including miRNA sponging, protein scaffolding, and translation. Their disease-specific roles make them promising candidates for clinical translation. This review highlights the potential of circRNAs as novel diagnostic tools and therapeutic targets in AP, aiming to guide future advancement of innovative biomarkers and therapeutic strategies.